L’INCIDENCE DES ARYTHMIES CARDIAQUES PRECOCES INDUITES PAR LE TRAITEMENT MEDICAL ONCOLOGIQUE. - BENMESSAOUD Fatma Anfal (My University, 2023)
The FAC protocol is the most arrhythmogenic, with 57% of the 3 molecules causing PAC premature atrial contaction and PVC premature ventricular Contraction type rhythm disorders. Conclusion: Arrhythmias are a common complication of certain anticancer drugs, underestimated, even by experienced clinicians. Rigorous, personalized management requires collaboration between oncologist and cardiologist throughout the cancer patient's care, following the prevention protocol established by ESC Guideliens 2022 according to risk stratification. Keywords: Arrhythmias, medical oncology, Cardiovascular toxicity risk stratification, prevention.
117 p.